Grace Ji-Sun Kim (ed.), Making Peace with the Earth: Action and Advocacy for Climate Justice - Haluza-DeLay, Randolph (Journal for the Study of Religion, Nature and Culture, 2018)
Grace Ji-Sun Kim (ed.), Making Peace with the Earth: Action and Advocacy for Climate Justice (Geneva: World Council of Churches Publications, 2016), 274pp., $25.00 (pbk), ISBN: 978-2-8254-1668-6.